(untitled) (Journal of Business Management and Accounting, 2024)
The study investigates the impact of celebrity endorsements on the sales performance of the beverage industry in Ghana, specifically focusing on the dimensions of celebrity credibility, popularity, and acceptance as key measures of the effectiveness of such endorsements. It addresses a notable gap in the literature by providing a clearer understanding of the factors firms can utilize to assess the strengths and weaknesses of potential celebrity endorsers in the Ghanaian context, particularly within the beverage industry. Data were collected from 100 respondents selected from the beverage industry. Hypotheses were tested using structural equation modeling (SEM) and partial least squares (PLS) to explore the relationships between variables. The findings reveal significant relationships between celebrity endorsements and sales performance, confirming the importance of considering popularity and credibility as critical measures in selecting celebrity endorsers to promote products. Based on the analyses and interpretations, the study recommends that firms intensify their use of popularity and credibility, along with attention to the acceptance of celebrities, to promote their products and safeguard brand image effectively.